The Importance Of Critical Thinking Skill To Vocational Students: Strategies And Benefits - Mardatillah, Oktariza; Prayudha.S, Joko (Akademi Komunitas Negeri Aceh Barat, 2024)
AbstractCritical thinking is one of the skills that are emphasized in 21st-century learning. This ability aims to make students competent at finding solutions and innovations to every problem they face in everyday life. Critical thinking teaches students to be prepared to be tough individuals and to find solutions to challenges that occur in their surroundings. Therefore, this study aims to explain how to promote the critical thinking skills of vocational students through various strategies and activities that can develop critical thinking skills as well as benefit learning. This research was carried out using qualitative methods through a library approach. The data in this study were obtained by collecting information from various sources, such as articles, books, and journals related to the application of critical thinking in learning, as well as documentation. Data analysis was carried out in three stages: data reduction, data display, and conclusions. Teachers can develop students' critical thinking skills in a variety of fun ways, both individually and in groups. Through improving critical thinking skills, students can become tough individuals who are ready to become responsible problem solvers. Teachers need to improve students' thinking skills by providing activities that can solve problems so that students can be more courageous in providing ideas and innovation from the activities they carry out. Keywords:Critical thinking; vocational; strategies; benefits. AbstrakBerpikir kritis merupakan salah satu kemampuan yang ditekankan pada pembelajaran abad 21. Kemampuan ini bertujuan agar siswa memiliki kompetensi yang baik dalam mencari solusi dan inovasi dari setiap permasalahan yang mereka hadapi dalam kehidupan sehari-hari. Berpikir kritis mengajarkan peserta didik untuk siap menjadi individu yang tangguh dan solutif terhadap tantangan yang terjadi dilingkungan sekitar. Oleh karena itu, penelitian ini bertujuan untuk menjelaskan bagaimana mempromosi kemampuan berpikir kritis siswa vokasi melalui berbagai strategi dan kegiatan yang dapat mengembangkan kemampuan berpikir kritis serta benefits dalam dalam pembelajaran. Penelitian ini dilaksanakan dengan menggunakan metode kualitatif melalui pendekatan kepustakaan. Data dalam penelitian ini didapatkan melalui pengumpulan informasi dari berbagai sumber seperti artikel, buku dan jurnal yang berkaitan dengan penerapan berpikir kritis dalam pembelajaran, serta dokumentasi. Analisa data dilakukan melalui tiga tahap yaitu data reduksi, data display, dan kesimpulan. Guru dapat mengembangkan kemampuan berpikir kritis siswa melalui berbagai cara yang menyenangkan baik secara individu maupun berkelompok. Melalui peningkatan kemampuan berpikir kritis siswa bisa menjadi individu yang tangguh dan siap menjadi problem solver yang bertanggung jawab. Guru perlu untuk meningkatkan kemampuan berpikir siswa secara baik melalui pemberian aktivtas yang dapat memecahkan masalah sehingga siswa dapat lebih berani dalam memberikan ide dan inovasi dari kegiatan yang mereka lakukan.Kata Kunci: Berpikir kritis; vokasi; strategi; manfaat.